Clinical Practice Guideline: Evaluation of the Neck Mass in Adults Executive Summary. (September 2017) - Pynnonen, Melissa A.; Gillespie, M. Boyd; Roman, Benjamin; Rosenfeld, Richard M.; Tunkel, David E.; Bontempo, Laura; Brook, Itzhak; Chick, Davoren Ann; Colandrea, Maria; Finestone, Sandra A.; Fowler, Jason C.; Griffith, Christopher C.; et al.
The American Academy of Otolaryngology—Head and Neck Surgery Foundation has published a supplement to this issue of Otolaryngology–Head and Neck Surgery featuring the "Clinical Practice Guideline: Evaluation of the Neck Mass in Adults." To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 12 recommendations developed emphasize reducing delays in diagnosis of head and neck squamous cell carcinoma; promoting appropriate testing, including imaging, pathologic evaluation, and empiric medical therapies; reducing inappropriate testing; and promoting appropriate physical examination when cancer is suspected.